Metabolic Adaptations May Counteract Ventilatory Adaptations of Intermittent Hypoxic Exposure during Submaximal Exercise at Altitudes up to 4000 m - Faulhaber, Martin (Public Library of Science, 2012)
Intermittent hypoxic exposure (IHE) has been shown to induce aspects of altitude acclimatization which affect ventilatory, cardiovascular and metabolic responses during exercise in normoxia and hypoxia. However, knowledge on altitude-dependent effects and possible interactions remains scarce. Therefore, we determined the effects of IHE on cardiorespiratory and metabolic responses at different simulated altitudes in the same healthy subjects. Eight healthy male volunteers participated in the study and were tested before and 1 to 2 days after IHE (7×1 hour at 4500 m). The participants cycled at 2 submaximal workloads (corresponding to 40% and 60% of peak oxygen uptake at low altitude) at simulated altitudes of 2000 m, 3000 m, and 4000 m in a randomized order. Gas analysis was performed and arterial oxygen saturation, blood lactate concentrations, and blood gases were determined during exercise. Additionally baroreflex sensitivity, hypoxic and hypercapnic ventilatory response were determined before and after IHE. Hypoxic ventilatory response was increased after IHE (p<0.05). There were no altitude-dependent changes by IHE in any of the determined parameters. However, blood lactate concentrations and carbon dioxide output were reduced; minute ventilation and arterial oxygen saturation were unchanged, and ventilatory equivalent for carbon dioxide was increased after IHE irrespective of altitude. Changes in hypoxic ventilatory response were associated with changes in blood lactate (r = −0.72, p<0.05). Changes in blood lactate correlated with changes in carbon dioxide output (r = 0.61, p<0.01) and minute ventilation (r = 0.54, p<0.01). Based on the present results it seems that the reductions in blood lactate and carbon dioxide output have counteracted the increased hypoxic ventilatory response. As a result minute ventilation and arterial oxygen saturation did not increase during submaximal exercise at simulated altitudes between 2000 m and 4000 m.